Preventing Respiratory Viruses in the Neonatal ICU. (4th October 2017) - Messina, Maria; Shui, Jessica; Maykowski, Philip; Leone, Tine; Saiman, Lisa
Abstract: Background: Infants in the neonatal ICU can acquire respiratory viruses from ill healthcare personnel (HCP), visitors, or other infants. We describe the epidemiology of respiratory viruses and infection prevention and control interventions aimed to reduce acquisition and transmission of respiratory viruses in our NICU. Methods: From May 2012 to December 2016, we tracked respiratory viruses detected by a multiplex reverse-transcriptase (RT)-PCR assay (FilmArray, Biofire, Inc.) in our 58-bed level IV NICU ( 1, 000 annual admissions). Testing was ordered by treating clinicians for symptomatic infants. Infants with positive RT-PCR tests generally remained on contact/ droplet precautions throughout their NICU stay. HCP were instructed not to work sick and report to Workforce Health and Safety if they became ill at work. Ill visitors were not permitted in the NICU, as enforced by written educational materials and signage, but formal screening was not performed. Starting in January 2015, asymptomatic infants exposed to RT-PCR-positive index cases were screened by RT-PCR, put on contact/ droplet precautions for the incubation period (IP) of the index case's virus, and screened again at IP end. Starting in December 2015, visitors <12 years old were banned year-round. We assessed dyad transmission events (2 infants), clusters (3 infants), and outbreaks (>3 infants); all were defined as detecting geographically related cases within the relevant IP. We determined screened infants who had positive RT-PCR tests. Results: During the 56 month observation period, 79 infants had 83 viruses detected ( 1.8% of admissions). Rhino/ enterovirus (RV/EV) were most common ( n = 59) and caused 1 outbreak of 7 infants, 4 clusters, and 5 dyad transmissions. Adenovirus caused 1 outbreak of 5 infants. Two dyad transmissions occurred for parainfluenza. Sporadic cases of RSV ( n = 5), coronavirus ( n = 5), and influenza ( n = 2) occurred. Ill household contacts were identified for 10 infants. No HCPs were identified with respiratory illnesses. Since January 2015, 8 screened infants had positive RT-PCR tests. Since December 2015, only 1 transmission dyad (RV/EV) occurred. Conclusion: Preliminary data suggest that our interventions have reduced the burden of respiratory viruses in the NICU. Disclosures: All authors: No reported disclosures.